An International Continence Society (ICS) report on the terminology for pelvic floor muscle assessment. Issue 5 (12th April 2021) - Frawley, Helena; Shelly, Beth; Morin, Melanie; Bernard, Stéphanie; Bø, Kari; Digesu, Giuseppe Alessandro; Dickinson, Tamara; Goonewardene, Sanchia; McClurg, Doreen; Rahnama'i, Mohammad S.; Schizas, Alexis; Slieker‐ten Hove, Marijke; et al.
Abstract: Introduction: The terminology for female and male pelvic floor muscle (PFM) assessment has expanded considerably since the first PFM function and dysfunction standardization of terminology document in 2005. New terms have entered assessment reports, and new investigations to measure PFM function and dysfunction have been developed. An update of this terminology was required to comprehensively document the terms and their definitions, and to describe the assessment method and interpretation of the finding, to standardize assessment procedures and aid diagnostic decision making. Methods: This report combines the input of members of the Standardisation Committee of the International Continence Society (ICS) Working Group 16, with contributions from recognized experts in the field and external referees. A logical, sequential, clinically directed assessment framework was created against which the assessment process was mapped. Within categories and subclassifications, each term was assigned a numeric coding. A transparent process of 12 rounds of full working group and external review was undertaken to exhaustively examine each definition, plus additional extensive internal development, with decision making by collective opinion (consensus). Results: A Terminology Report for the symptoms, signs, investigations, and diagnoses associated with PFM function and dysfunction, encompassing 185 separate definitions/descriptors, has been developed. It is clinically based with the most common assessment processes defined. Clarity and user‐friendliness have been key aims to make it interpretable by clinicians and researchers of different disciplines. Conclusion: A consensus‐based Terminology Report for assessment of PFM function and dysfunction has been produced to aid clinical practice and be a stimulus for research.